Longitudinal Analysis of Quality of Life, Clinical, Radiographic, Echocardiographic, and Laboratory Variables in Dogs with Myxomatous Mitral Valve Disease Receiving Pimobendan or Benazepril: The QUEST Study. (6th September 2013) - Häggström, J.; Boswood, A.; O'Grady, M.; Jöns, O.; Smith, S.; Swift, S.; Borgarelli, M.; Gavaghan, B.; Kresken, J.‐G.; Patteson, M.; Åblad, B.; Bussadori, C.M.; et al.
<x xml:space="preserve">Abstract</x> Background Myxomatous mitral valve disease (MMVD) is an important cause of morbidity and mortality in dogs. Objectives To compare, throughout the period of follow‐up of dogs that had not yet reached the primary endpoint, the longitudinal effects of pimobendan versus benazepril hydrochloride treatment on quality‐of‐life (QoL) variables, concomitant congestive heart failure (CHF) treatment, and other outcome variables in dogs suffering from CHF secondary to MMVD. Animals A total of 260 dogs in CHF because of MMVD. Methods A prospective single‐blinded study with dogs randomized to receive pimobendan (0.4–0.6 mg/kg/day) or benazepril hydrochloride (0.25–1.0 mg/kg/day). Differences in outcome variables and time to intensification of CHF treatment were compared. Results A total of 124 dogs were randomized to pimobendan and 128 to benazepril. No difference was found between groups in QoL variables during the trial. Time from inclusion to 1st intensification of CHF treatment was longer in the pimobendan group (pimobendan 98 days, IQR 30–276 days versus benazepril 59 days, IQR 11–121 days; P = .0005). Postinclusion, dogs in the pimobendan group had smaller heart size based on VHS score (P = .013) and left ventricular diastolic (P = .035) and systolic (P = .0044) dimensions, higher body temperature (P = .030), serum sodium (P = .0027), and total protein (P = .0003) concentrations, and packed cell volume (P = .030). Incidence of arrhythmias was similar in treatment groups. Conclusions and Clinical Importance Pimobendan versus benazepril resulted in similar QoL during the study, but conferred increased time before intensification of CHF treatment. Pimobendan treatment resulted in smaller heart size, higher body temperature, and less retention of free water.